2011
DOI: 10.1038/onc.2011.207
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin is key regulator of Src-induced malignant phenotype in three-dimensional environment

Abstract: The oncogenic tyrosine kinase Src has a role in cancer development, especially by promoting invasive and metastatic behavior. It is, however, unclear which of the Srcregulated signaling cascades induce malignant phenotype in three-dimensional environment. One of Src substrates is ezrin, a cytoskeletal organiser and regulator of signal transduction. Ezrin expression correlates with poor outcome of diverse cancers and is essential in experimental metastatic osteosarcoma. We reconstituted genetically ezrin-defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 46 publications
3
35
0
Order By: Relevance
“…In doing so, rounding makes mitosis robust to the environment. Moreover, this may explain the identification of key regulators of mitotic rounding, particularly Ect2 and the ERM family proteins, as oncogenes associated with metastasis and capable of transforming cells to grow in soft agar [28,30]. If these ideas are borne out in experiments, it will be important to reassess the roles of the many other actin cytoskeletal regulators that have been implicated in cancer progression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In doing so, rounding makes mitosis robust to the environment. Moreover, this may explain the identification of key regulators of mitotic rounding, particularly Ect2 and the ERM family proteins, as oncogenes associated with metastasis and capable of transforming cells to grow in soft agar [28,30]. If these ideas are borne out in experiments, it will be important to reassess the roles of the many other actin cytoskeletal regulators that have been implicated in cancer progression.…”
Section: Resultsmentioning
confidence: 99%
“…Ect2 is up-regulated in a number of cancers including lung, brain, ovarian and bladder [27], and when silenced by RNAi, leads to reduced invasion, tumorigenicity and growth in soft agar in lung cancer cells [28]. Similarly, Ezrin is over-expressed in a huge range of cancer types [29] and has been shown to be essential for metastasis and anchorage independent growth in soft agar [30]. Yet despite well-established links with tumorigenesis, the molecular function of Ect2 or Ezrin in the context of cancer has not been addressed in great detail.…”
Section: Ect2 and Erm Proteins In Mitotic Rounding And Cancer Metastasismentioning
confidence: 99%
“…Altered expression of a subset of 4.1 family proteins is believed to contribute to carcinogenesis and metastasis, as exemplified by the following: merlin has been shown to function as a tumor suppressor [9]; ezrin is believed to play a role in the development of metastasis [10,11]; moesin has been implicated in oral squamous cell carcinomas [12][13][14]; and willin has been shown to antagonize some of the functions of the YAP oncogene [6]. We have shown previously that a high level of cytoplasmic ezrin correlates or that high levels of cytoplasmic ezrin correlate with poor survival in head and neck squamous cell carcinoma [15], and recent studies show that increased expression of ezrin is also associated with poor clinical outcome in a variety of human cancers [16][17][18][19][20][21].…”
mentioning
confidence: 99%
“…Further evidence links phosphorylation on Ezrin Y146 to Src-dependent adhesion signalling promoting cell proliferation (Srivastava et al, 2005) and nominates another Src-phosphorylated residue Y477 as the effector of a malignant phenotype in Src-transformed cells (Heiska and Carpen, 2005;Heiska et al, 2011), supported again by a recent report from Mak et al (2012) proposing a role for phosphorylation of Y477 in invasion and migration.…”
Section: Discussionmentioning
confidence: 77%
“…Ezrin is also of interest from a cancer perspective, with an established role in metastasis (Brambilla and Fais, 2009;Fais, 2004;Federici et al, 2009;Zhou et al, 2010a) and an emerging role in proliferative signalling (Gautreau et al, 1999;Heiska et al, 2011;Kishore et al, 2005;Srivastava et al, 2005). Ezrin has been previously shown to be increased in leukaemic cells (Monni et al, 2008) and has been identified as a target of oncogenic signalling from extracellular signalling mediators PDGF, EGF and HGF as well as intracellular oncogenic kinases Src, Lck and Rho (Crepaldi et al, 1997;Fazioli et al, 1993;Monni et al, 2008).…”
Section: Discussionmentioning
confidence: 99%